2015
DOI: 10.1128/microbiolspec.mb-0017-2015
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus Biofilm In Vitro and In Vivo

Abstract: In vivo, Aspergillus fumigatus grows as a typical biofilm with hyphae covered by an extracellular matrix (ECM) composed of polysaccharides, galactomannan, and galactosaminogalactan. α1,3 glucans and melanin are also constitutive of the ECM in aspergilloma but not in invasive aspergillosis. In vitro, two biofilm models were established to mimic the in vivo situation. The first model (model 1) uses submerged liquid conditions and is characterized by slow growth, while the second model (model 2) uses agar medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 60 publications
2
43
0
2
Order By: Relevance
“…[26] as swollen conidia started germination between 4 and 8 h in order to form a monolayer of hyphae, followed by an intense filamentation to create a complex hyphal network at 24 h of culture (Fig 2A). The production of ECM in the fungal biofilm was visible at 12 h and increased until 24 h, the maturation phase, where the fungi was totally covered by the matrix (Fig 2), in consistency with the results of Beauvais and Latgé [18]. The microscopic analyses of this biofilm helped visualise the hyphae in the ECM which formed a resistant structure covering the hyphae and the spaces between them (Fig 2B) [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[26] as swollen conidia started germination between 4 and 8 h in order to form a monolayer of hyphae, followed by an intense filamentation to create a complex hyphal network at 24 h of culture (Fig 2A). The production of ECM in the fungal biofilm was visible at 12 h and increased until 24 h, the maturation phase, where the fungi was totally covered by the matrix (Fig 2), in consistency with the results of Beauvais and Latgé [18]. The microscopic analyses of this biofilm helped visualise the hyphae in the ECM which formed a resistant structure covering the hyphae and the spaces between them (Fig 2B) [21].…”
Section: Discussionsupporting
confidence: 85%
“…In vitro , biofilms with single A . fumigatus [1821] or S . maltophilia [2224] showed standard growth, yet and to our knowledge, no study on mixed biofilm of these two organisms has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Such structural differences were observed in the chitin microfibrils of the mycelium cell wall of chs mutant, which have either short or long microfibrils while their content in chitin is similar (Muszkieta et al, ). This is also seen in the localization of the α1,3 glucans, which is different in both morphotypes (Beauvais & Latgé, ). These studies indicated that the structural organization of the cell wall polysaccharides and their modifications during morphological changes remain poorly understood.…”
Section: Discussionmentioning
confidence: 94%
“…These studies have provided extensive knowledge of the effect of different variables, including growth time, nutrients, and physiological conditions, on biofilm formation, morphology, and architecture ( 15 ). In this chapter, we will focus on Candida biofilms (biofilms caused by Aspergillus are covered in reference 155 ) and provide an update on their development, architecture, and resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%